Harmony in Diversity in Border Areas: Dayak Iban Tribe and Migrants in Badau - Segara, I Nyoman Yoga; Kustini, Kustini; Mustolehudin, Mustolehudin; Muawanah, Siti; Nofandi, R. Adang (UIN Maulana Malik Ibrahim Malang, 2024)
This study aimed to highlight the harmonious coexistence among different ethnic and religious groups. The study was conducted in Badau, a sub-district in West Kalimantan, inhabited by the indigenous Dayak Iban ethnic group and migrants from various ethnic and religious backgrounds. The primary motivation for examining the socio-cultural and religious life in Badau stems from the region's challenges, including limited religious guidance and services, the establishment of places of worship, the roles of traditional and religious leaders, and interfaith relationships. Using a qualitative approach with observation, interviews, and document analysis, the research revealed several key findings. Firstly, customary rules play a significant role in the lives of the Dayak Iban, serving as a guiding principle. They adhere to these rules strictly but with flexibility. Secondly, community leaders and social institutions are instrumental in resolving social issues. The rumah panjang and balai adat are two key mechanisms for conflict resolution. The study recommends conducting anthropological and historical research to trace the origins of the Dayak Iban tribe and explore religious encounters in the region. It also suggests that local governments in border areas emulate Badau’s community resilience, where the Cross-Border Post (PLBN) serves as a living symbol of unity, promoting nationalism and harmony among diverse ethnic, cultural, and religious groups. Studi ini bertujuan untuk menyoroti kehidupan harmonis di antara kelompok etnis dan agama yang berbeda. Penelitian ini dilakukan di Badau, sebuah kecamatan di Kalimantan Barat, yang dihuni oleh suku Dayak Iban sebagai kelompok etnis asli dan para migran dari berbagai latar belakang etnis dan agama. Motivasi utama untuk meneliti kehidupan sosial budaya dan agama di Badau berasal dari tantangan yang dihadapi wilayah ini, seperti keterbatasan bimbingan dan layanan keagamaan, pendirian tempat ibadah, peran pemimpin adat dan agama, serta hubungan antar umat beragama. Dengan menggunakan pendekatan kualitatif melalui observasi, wawancara, dan studi dokumen, penelitian ini mengungkapkan beberapa temuan penting. Pertama, aturan adat memainkan peran penting dalam kehidupan suku Dayak Iban, menjadi pedoman utama mereka. Mereka mematuhi aturan tersebut dengan tegas namun fleksibel. Kedua, para pemimpin komunitas dan lembaga sosial berperan penting dalam menyelesaikan masalah sosial. Rumah panjang dan balai adat merupakan dua mekanisme penyelesaian konflik di antara masyarakat. Studi ini merekomendasikan dilakukannya penelitian antropologi dan sejarah untuk menelusuri asal-usul suku Dayak Iban serta mengeksplorasi pertemuan agama di wilayah tersebut. Studi ini juga menyarankan agar pemerintah daerah di wilayah perbatasan meniru ketahanan komunitas di Badau, di mana Pos Lintas Batas Negara (PLBN) berfungsi sebagai simbol hidup persatuan, mempromosikan nasionalisme dan kerukunan di antara kelompok etnis, budaya, dan agama yang beragam.